Field Data Report for the First Microwave Water and Energy Balance Experiment (MicroWEX-1), July 17 - December 16, 2003, Citra, Florida - Kai-Jen Calvin Tien; Jasmeet Judge; Larry W. Miller; Orlando L. Lanni (EDIS)
Many studies have been conducted in agricultural areas such as bare soil, grass, soybean, wheat, pasture, and corn to understand the relationship between soil moisture and microwave remote sensing. Most of these experiments conducted in agricultural regions have been short-term experiments that captured only a part of growing seasons. It is important to know how microwave brightness signature varies with soil moisture, evapotranspiration (ET), and biomass in a dynamic agricultural canopy with a significant biomass (4-6 kg/m2 ) throughout the growing season. This document is Circular 1470, one of a series of the Agricultural and Biological Engineering Department, Agricultural Research Station, Institute of Food and Agricultural Sciences, University of Florida. First published April 2005.